Investigation of Solid Waste Characterization, Composition and Generation Using Management of Environmental Systems in Zarqa, Jordan - K. Younes, Mohammad; Nopiah, Z.M.; Nadi, B.; Ahmad Basri, N.E.; Basri, Hassan; F.M. Abushammala, Mohammed; Shatanawi, Khaldoun (Asian Journal of Chemistry, 2013)
Municipal solid waste management is a critical environmental challenge facing the development. Solid waste characteristics change with time due to changes in the population’s consumption and lifestyle. Characterization of solid waste helps the decision makers take the sustainable actions. This is the first study that introduces integrated solid waste management principles in Zarqa, Jordan. The results indicate that the total solid waste generation is approximately 299 tons/day, with a generation rate of 0.69 kg/capita per day. By 2030, it is expected to reach 446 tons/day, with a generation rate of about 0.75 kg/capita per day. The organic fraction is 48.9 %, while the other main components like paper and cardboard and plastics are 13.3 and 15.2 %, respectively. The heat content is between 2,121 and 2,905 kcal/kg. A high organic content requires special considerations for waste handling and disposal. Moreover, it gives preference to composting over other heat recovery techniques.